2013
DOI: 10.1016/j.ajpath.2013.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Side-Specific Endothelial-Dependent Regulation of Aortic Valve Calcification

Abstract: Arterial endothelial cells maintain vascular homeostasis and vessel tone in part through the secretion of nitric oxide (NO). In this study, we determined how aortic valve endothelial cells (VEC) regulate aortic valve interstitial cell (VIC) phenotype and matrix calcification through NO. Using an anchored in vitro collagen hydrogel culture system, we demonstrate that three-dimensionally cultured porcine VIC do not calcify in osteogenic medium unless under mechanical stress. Co-culture with porcine VEC, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 44 publications
6
133
2
Order By: Relevance
“…Oxidative stress has been shown to participate in the development of CAVD (Miller et al 2008;Kennedy et al 2009;Li and Förstermann 2013) and be associated with local hemodynamic changes (Richards et al 2013). NOS3, commonly known as eNOS, has long been known for its protective effects against aortic valve inflammation and calcification (Clapp et al 2004;Kennedy et al 2009).…”
Section: Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress has been shown to participate in the development of CAVD (Miller et al 2008;Kennedy et al 2009;Li and Förstermann 2013) and be associated with local hemodynamic changes (Richards et al 2013). NOS3, commonly known as eNOS, has long been known for its protective effects against aortic valve inflammation and calcification (Clapp et al 2004;Kennedy et al 2009).…”
Section: Modulementioning
confidence: 99%
“…4B). According to the literature, NOS3 is a mechano-sensitive gene that is regulated by the flow-sensitive KLF2 transcription factor (SenBanerjee et al 2004;Richards et al 2013). The findings suggest that there is a close relationship between hemodynamics and endothelial oxidative stress in the development of CAVD.…”
Section: Modulementioning
confidence: 99%
“…The ventricularis experiences unidirectional laminar shear stress as blood is ejected from the ventricle to the aorta. The fibrosa experiences disturbed flow and oscillatory shear stress, as shown in Figure 2B, which have been directly linked to onset and progression of CAVD (6,40,104). Shear stress regulates endothelial cell function: the cells sense changes in shear stress to determine systemic changes, such as hypertension.…”
Section: Fig 2 Major Forces Affecting Aortic Valve (A)mentioning
confidence: 99%
“…Bosse et al (14) studied the role of NO in aortic valve calcification using a coculture system of endothelial cells and aortic valve interstitial cells (AVICs) and found that endothelial cells secrete NO, which is absorbed by AVICs, preventing calcification through regulation of the Notch1 signaling pathway in AVICs. Richards et al (104) found that in both calcified and noncalcified human aortic valves, the ventricularis side exhibited a threefold higher expression of eNOS compared with the fibrosa. Interestingly, the calcified valves presented lower values of eNOS expression on both sides compared with healthy aortic valves.…”
Section: Notch Signaling Pathwaysmentioning
confidence: 99%
“…Bound Alizarin red S dye was then released from the gels using 10% acetic acid, followed by neutralization with 10% ammonium hydroxide. 36 The absorbance of the dye solution was measured at 405 nm.…”
Section: Duan Et Almentioning
confidence: 99%